TANTANGAN DAN PELUANG PEMBELAJARAN KOSAKATA (Studi di Program Studi PBI STAIN Jurai Siwo Metro) - Irwansyah, Dedi (P3M STAIN Jurai Siwo Metro, 2012)
AbstractÂ The concept of English vocabulary might have been overgeneralized as a list of words to note or to memorize. Â The concept is full of technical terms to digest such as word family, lexeme, multi-words unit, polysemy, collocation, connotation, idiom, and so forth. In teaching vocabulary, then, those terms ought to be considered in line with the effort of finding out the approach the teacher finds useful. This would be much more effective when the supports from the institution, in the form of policies, are available. The purpose of this research is to identify the challenges and opportunities of teaching English vocabulary within a specific formal education background called English Language Teaching Department of STAIN Jurai Siwo Metro. Such purposes are viewed in the perspective of the possible policies that could be implemented by the department. Therefore, a policy research consisting of four phases is used. The phases involve identifiying issues and problems, understanding key issues, setting up treatments, and monitoring and evaluating the progress. This research suggests that the department or institution pursue such policies as setting up a standardization of English-English dictionary, implementing the minimum requirement of vocabulary competency, and shifting paradigm or approach of teaching vocabulary. A lexical approach is highly recommended for it embraces the related technical terms within the concept of English vocabulary.Keywords: Vocabulary, word family, policy research, lexical approach.